Markets, Distance Education, and Australian Higher Education - Nunan, Ted (International Review of Research in Open and Distributed Learning, 2005)
The paper argues that the Australian university system is unstable. There will be significant change as government implements its reform agenda and even more radical change if it moves to new deregulation. The role of distance education in university education needs to be analyzed against this "market" agenda of government in terms of characteristics of markets and market behavior. After a scan of the current role, the paper looks at two scenarios (regulated and deregulated) for distance education in university teaching and learning in Australia.